If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 752 = 4x + 16 Reorder the terms: 752 = 16 + 4x Solving 752 = 16 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 752 + -4x = 16 + 4x + -4x Combine like terms: 4x + -4x = 0 752 + -4x = 16 + 0 752 + -4x = 16 Add '-752' to each side of the equation. 752 + -752 + -4x = 16 + -752 Combine like terms: 752 + -752 = 0 0 + -4x = 16 + -752 -4x = 16 + -752 Combine like terms: 16 + -752 = -736 -4x = -736 Divide each side by '-4'. x = 184 Simplifying x = 184
| 144=12(x+1) | | 15x+6=15x+6 | | y+x=zx | | 13=9x-4 | | 5+12x=3+18x | | ln(x)+ln(x^2-8)=ln(8x) | | 7x-15+8-15=180 | | 8(1+4b)+8b=128 | | 20y-15y=20 | | -8x-18=-12x+34 | | 3x/2+7x-7=3(2x+1) | | 2a+2a=2a | | 17-(3m+7)=2+3m-16 | | 3(4z+8)-36= | | -8-18=-12+34 | | -20D-3+3D=11D+5-8 | | 80.5=7(m+3.6) | | 5+44x=53+8x | | 7=9x-7 | | 7z-7=5+32 | | b=4b | | 34.95(5)+x(.49)=200 | | 6+7x=-8 | | 3(x-6)=2 | | -11-5(t-3)= | | y=(x^2+1)(12x)-(6x^2+7)(2x) | | 44-5x=53-8x | | 7(x-2)+2=-12 | | .10x+.35(50)=23.5 | | 4y+6=8y+2 | | 13x-203=6x-7 | | 5+2t-2=6t+9-2t |